Encyclopaedia of religion and ethics - Hastings, James; Selbie, John A.; Gray, Louis H. (Charles Scribner's Sons, 1908)
v. 1. A-Art -- v. 2. Arthur-Bunyan -- v. 3. Burial-Confessions -- v. 4. Confirmation-Drama -- v. 5. Dravidians-Fichte -- v. 6. Fiction-Hyksos -- v. 7. Hymns-Liberty -- v. 8. Life and death-Mulla -- v. 9. Mundas- Phrygians -- v. 10. Picts-Sacraments -- v. 11. Sacrifice-Sudra -- v. 12. Suffering-Zwingli -- v. 13. Indexes.